2003
DOI: 10.1542/peds.112.4.e325
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Live Viral Vaccines in Patients With Chromosome 22q11.2 Deletion Syndrome (DiGeorge Syndrome/Velocardiofacial Syndrome)

Abstract: Live attenuated viral vaccines are a part of routine childhood immunizations and over the years have proved their safety and efficacy in the general population. Mild adverse effects of measles-mumps-rubella (MMR) vaccination include fever, rash, and lymphadenopathy and occur in approximately 5% to 15% of vaccine recipients. 1,2 Similarly, side effects of the varicella vaccine include injection site reactions, fever, and rash, which occur in 5% to 30% of individuals. [3][4][5] Severe side effects are exceedingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
51
0
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 6 publications
(6 reference statements)
6
51
0
18
Order By: Relevance
“…[13][14][15] Few serious events were temporally associated with live vaccination, and none were assessed to be causally associated with live vaccination. These data are consistent with earlier studies 10,11,16,17 and suggest that live vaccines may be given safely to some patients with DGS. The benefits of MMR and varicella vaccination, in particular, appear to outweigh the potential risks for patients with DGS with mild-tomoderate immunosuppression.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…[13][14][15] Few serious events were temporally associated with live vaccination, and none were assessed to be causally associated with live vaccination. These data are consistent with earlier studies 10,11,16,17 and suggest that live vaccines may be given safely to some patients with DGS. The benefits of MMR and varicella vaccination, in particular, appear to outweigh the potential risks for patients with DGS with mild-tomoderate immunosuppression.…”
Section: Discussionsupporting
confidence: 91%
“…10 Another study reported higher rates of varicella illness among unvaccinated patients with DGS, which could reflect greater disease exposure, lower vaccine uptake, or less herd immunity. 11,33 In our study, the paucity of severely immunosuppressed subjects could explain why there were relatively few AEFLIs despite high vaccination coverage. In support of this, patients with an AE after varicella vaccination had lower preceding CD4% (24.8%) versus those who did not (35.5%).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations